The clinical characteristics, complications and treatment outcomes of patients with osteoporosis at Groote Schuur Hospital - Abdelfadiel, Omer Alawad Homaida (Department of Medicine, 2021)
Background: Osteoporosis has become a major problem worldwide as the population ages. An osteoporotic fracture is associated with a high rate of morbidity and mortality. Data on the prevalence, risk factors and outcome of osteoporotic fractures in South Africa remains sparse. Method: A retrospective audit was undertaken in all patients attending the Endocrine Clinic at Groote Schuur Hospital between March 2019 and March 2020 for the treatment of osteoporosis. Patients folders were reviewed to obtain the following information: demographic data, risk factors, laboratory investigations, treatment, baseline and follow up DEXA scans. Results: 264 patients were evaluated, average age 65.7 ± 12.3 years, 92.8% (n=245) were female. Common risk factors included smoking (50.8%, n=134), vitamin D deficiency (29.2%, n=77), steroid use (21.6%, n=57) and primary hyperparathyroidism (15.2%, n=40). A fragility fracture was diagnosed in 68.6% (n=181) - vertebral only (54.7%, n=99), hip only (14.9%, n=27), vertebral and hip (10.5%, n=19), wrist (7.2%, n=13) and other (12.7%, n=23). Bisphosphonates were used by 75% (n=198) of patients at the time of enrolment. Of these, 80.8% (n=160) received intravenous zoledonic acid alone, 6.1% (n=12) received oral alendronate alone and 13.1% (n=26) initially received alendronate followed by intravenous zoledronic acid. Over 5.2 years there was an improvement in bone mineral density (BMD) of 4.4% at the lumbar spine, while there was slight worsening of BMD at the femoral neck (- 0.17%). A fracture whilst on treatment occurred in 10.6% (n=21) of patients. Conclusion: The majority of patients with osteoporosis at Groote Schuur Hospital had a fragility fracture at diagnosis with a vertebral fracture being most common. Bisphosphonate treatment showed a measurable improvement in BMD at the lumbar spine, however, there was no improvement at the femoral neck. Despite this, few patients had a symptomatic vertebral or hip fracture whilst on treatment.